Injectable MXene/Ag-HA composite hydrogel for enhanced alveolar bone healing and mechanistic study - Li, Jialing; Fan, Zilu; Guan, Zhenju; Ruan, Jianping (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction Alveolar bone defects pose significant challenges in dentistry. Due to the complexity of alveolar bone anatomy and insufficient repair mechanisms, large bone defects are difficult for the body to heal naturally. Clinical treatment typically involves the use of bone substitute materials. However, current substitutes often suffer from limitations such as insufficient osteoinductivity, rapid degradation, inflammatory responses, and poor mechanical properties. Additionally, the irregular morphology of alveolar bone defects complicates the application of solid bone substitutes, potentially leading to secondary damage at the repair site. Methods To address these challenges, this study introduces an innovative approach by integrating MXene nanomaterials into Ag-HA/GelMA hydrogels to create an injectable MXene/Ag-HA composite hydrogel. MXene nanomaterials are renowned for their excellent biocompatibility, antibacterial properties, and mechanical strength. Results The results indicate that the MXene/Ag-HA composite hydrogel exhibits satisfactory mechanical and biological properties. Specifically, it demonstrates excellent antibacterial, antioxidant, and osteogenic activities. Gene expression analysis further reveals that the MXene composite hydrogel promotes osteogenesis by regulating the expression of Dmp1 and Dusp1. Discussion The findings of this study suggest that the MXene/Ag-HA composite hydrogel is a promising candidate for alveolar bone repair and regeneration. The integration of MXene nanomaterials into the hydrogel enhances its mechanical and biological properties, making it well-suited for the treatment of irregular alveolar bone defects. Furthermore, the study underscores the vast potential of MXene nanomaterials in the biomedical field, hinting at potential applications beyond alveolar bone repair.